Acute Liver Failure Due to Toxoplasmosis After Orthotopic Liver Transplantation. (May 2021) - Baldwin, Nicholas; Gray, Meagan; Patel, Chirag R.; Al Diffalha, Sameer
Solid organ transplant recipients are at risk for a wide range of opportunistic infections, the most common being cytomegalovirus. These infections may occur as reactivation of latent disease, donor-derived, or de novo. In this article, we present a case of acute liver failure secondary to toxoplasmosis following orthotopic liver transplantation. Our patient presented 5 weeks after orthotopic liver transplantation with altered mental status and fatigue. She was found to have disseminated cytomegalovirus infection, which resolved with intravenous ganciclovir; however, she subsequently developed acute liver failure due to toxoplasmosis, which is hypothesized to be donor-derived. Infection with Toxoplasma may be asymptomatic in the immunocompetent host; however, in immunocompromised hosts, such as solid organ transplant recipients, this infection can be life threatening. Though prophylaxis with trimethoprim-sulfamethoxazole may prevent infections with Toxoplasma, it is often held for renal dysfunction, hyperkalemia, or other side effects, placing patients at risk. With 13 cases now reported, routine screening of donor and recipient for toxoplasma exposure may be warranted.